Parallel processing in computational mechanics - Adeli, Hojjat (New generation computing, 1992)
Introduces mechanical engineers to high-performance computing using the new generation of computers with vector and parallel processing capabilities that allow the solution to problems beyond the ken of traditional computers. The chapters present an introduction and overview, explain several methodo